Globorentonium, a new genus of rentoniine Trogossitidae (Coleoptera: Cleroidea) from Australia and Brazil - Lawrence, John F.; Slipinski, Adam (Zootaxa, 2013)
A new genus of Rentoniini, Globorentonium gen. n., is described including three new species: G. globulum sp. n. (type species) from Tasmania, Victoria, ACT and southern New South Wales; G. lescheni sp. n. from northern New South Wales and G. plaumanni sp. n. from southern Brazil. The new genus is compared with other known genera of Rentoniinae, and a key to world genera is provided.